(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The thesis presents a comparative analysis of international standards (ISO 25745, EN 115, ASME A17) and Uzbekistan’s regulatory documents governing metro escalator safety. Through document analysis, the main requirements, scope, and differences between standards have been identified. The study reveals gaps in Uzbekistan’s regulatory framework and proposes recommendations for their elimination.